2018
DOI: 10.1158/0008-5472.can-17-1679
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Activities Enhance Markers of Drug Sensitivity in Cancer

Abstract: Transcriptional dysregulation induced by aberrant transcription factors (TF) is a key feature of cancer, but its global influence on drug sensitivity has not been examined. Here, we infer the transcriptional activity of 127 TFs through analysis of RNA-seq gene expression data newly generated for 448 cancer cell lines, combined with publicly available datasets to survey a total of 1,056 cancer cell lines and 9,250 primary tumors. Predicted TF activities are supported by their agreement with independent shRNA es… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
213
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(218 citation statements)
references
References 51 publications
5
213
0
Order By: Relevance
“…We then investigated if these differences in dynamic behavior could be derived from their genetic makeup (Garcia‐Alonso et al , ). From the proteins in our model, only KRAS is functionally mutated in AsPC1 and TP53 in BxPC3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then investigated if these differences in dynamic behavior could be derived from their genetic makeup (Garcia‐Alonso et al , ). From the proteins in our model, only KRAS is functionally mutated in AsPC1 and TP53 in BxPC3.…”
Section: Resultsmentioning
confidence: 99%
“…These differences in the model parameters cause changes in the dynamic behavior of the system ( Fig 2B) and are behind the differential activation of Cas3 in response to drugs. We then investigated if these differences in dynamic behavior could be derived from their genetic makeup (Garcia-Alonso et al, 2018). From the proteins in our model, only KRAS is functionally mutated in AsPC1 and TP53 in BxPC3.…”
Section: Calibration Of the Apoptosis Model For Cell Linesmentioning
confidence: 99%
“…First, we assessed the activity of transcription factors (TFs; Figure 3), based the levels of expression of their known putative targets (see Methods). Changes in putative target genes provided superior estimates of the TF activity than the expression level of the transcription factor itself 18,19 (Figure 3). We found 10 TFs differentially regulated in at least one CKD entity ( Figure 3).…”
Section: Transcription Factor Activity In Ckd Entitiesmentioning
confidence: 99%
“…We estimated transcription factor activities in the glomerular CKD entities using DoRothEA 18 which is a pipeline that tries to estimate transcription factor activity via the expression level of its target genes utilizing a curated database of transcription factor -target gene interactions (TF Regulon). For more information see Supplementary Methods.…”
Section: Transcription Factor Activity Analysismentioning
confidence: 99%
“…In one study, ENCODE ChIP-seq data were integrated with RNA-seq data to identify drugs that might alter TF activity in specific diseases [**68]. In another study, Chen et al showed that they could use ENCODE data to identify genome-wide signatures of TF activity and proposed that these signatures could be utilized to identify new candidate drugs [69].…”
Section: Introductionmentioning
confidence: 99%